Empowerment of Food MSMEs Based on Local Wisdom in Ladang Bambu Village - A M Hatuaon Sihite; Ikwan Lubis; Maringan Sianturi; Nurin Natiqoh Lubis (Journal of Economics, Management and Accounting (JEMA), 2024)
Empowering Micro, Small, and Medium Enterprises (MSMEs) based on local wisdom plays a crucial role in improving the local economy while preserving regional culture. This study aims to analyze the empowerment strategies of local wisdom-based food MSMEs in Ladang Bambu Village. The method used involves a participatory approach through training, mentoring, and market access strengthening. The results indicate that the preservation of traditional recipes, the use of local ingredients, and attractive packaging are key to success. Furthermore, collaboration with the government and private institutions is essential to provide support in terms of facilities, technology, and marketing. In conclusion, empowering MSMEs based on local wisdom not only improves community welfare but also preserves local cultural identity. The implementation of MSME empowerment strategies for food-based local wisdom in Ladang Bambu Village plays an important role in boosting the local economy while preserving culture through local food products. The research method employed in this study is a qualitative approach, with data collection techniques including interviews, observations, and literature studies. The findings show that the potential for local wisdom-based food in Ladang Bambu Village can be developed through business management training, product innovation, digital marketing, and increased access to capital. The main challenges faced are limited knowledge of technology, limited market access, and a lack of understanding of business management. Therefore, collaboration between the government, MSME actors, and the community is necessary to create an ecosystem that supports the sustainability of local wisdom-based enterprises.